2017
DOI: 10.1016/j.quaint.2014.12.053
|View full text |Cite
|
Sign up to set email alerts
|

Carbon isotope signatures from land snail shells: Implications for palaeovegetation reconstruction in the eastern Mediterranean

Abstract: In this study we compare carbon isotope values in modern Helix melanostoma shell carbonate (δ 13

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 52 publications
(59 reference statements)
5
30
0
Order By: Relevance
“…Yanes et al (2018) also observed little difference in offsets of δ 13 C shell -δ 13 C SBOM and δ 13 C shell -δ 13 C body for the snail, Neohelix, in North Carolina (USA), and their CIF values were +14.1‰ and +14.5‰, respectively. A similar positive offset of 14.5‰ was determined for δ 13 C shell relative to δ 13 C body of Helix melanostoma in the eastern Mediterranean (Prendergast et al, 2017). In addition, the regression line between δ 13 C shell and δ 13 C SBOM /δ 13 C body for Cathaica in this study and that of Liu, Gu, et al (2007) are indistinguishable from that for Helix aspersa developed in a culturing study (Stott, 2002).…”
Section: Journal Of Geophysical Research: Biogeosciencessupporting
confidence: 78%
See 1 more Smart Citation
“…Yanes et al (2018) also observed little difference in offsets of δ 13 C shell -δ 13 C SBOM and δ 13 C shell -δ 13 C body for the snail, Neohelix, in North Carolina (USA), and their CIF values were +14.1‰ and +14.5‰, respectively. A similar positive offset of 14.5‰ was determined for δ 13 C shell relative to δ 13 C body of Helix melanostoma in the eastern Mediterranean (Prendergast et al, 2017). In addition, the regression line between δ 13 C shell and δ 13 C SBOM /δ 13 C body for Cathaica in this study and that of Liu, Gu, et al (2007) are indistinguishable from that for Helix aspersa developed in a culturing study (Stott, 2002).…”
Section: Journal Of Geophysical Research: Biogeosciencessupporting
confidence: 78%
“…The shallower slope at higher rainfall levels is in accordance with the changing pattern of C 3 plant δ 13 C with precipitation on a global scale (Kohn, ). The inference that water stress (water use efficiency) in plants is recorded in snails (determined using snail δ 13 C shell ) has previously been confined to only C 3 ‐plant dominated landscapes (e.g., Colonese et al, ; Prendergast et al, ; Yanes, ). We extended it to different landscapes in this study.…”
Section: Discussionmentioning
confidence: 99%
“…δ 13 CTOC values range from -22.8 ‰ to -25.5 ‰. These values are similar to topsoils dominated by C3 vegetation in the Mediterranean region (e.g., Hartman and Danin, 2010;Prendergast et al, 2017). Through the core δ 13 CTOC range from -26‰ to -34 ‰.…”
Section: Resultsmentioning
confidence: 61%
“…Surveys we conducted across the Gebel Akhdar demonstrated that settlement increasingly concentrated in the better watered more forested parts of the landscape (Jones et al 2016). Isotope analysis of land snails supports the conclusion that the Gebel Akhdar was a refugium for plants, animals and people at this time as the Sahara became desert (Prendergast et al 2016b(Prendergast et al , 2017. The use of the cave appears to have intensified significantly with deglaciation after the LGM, by people using Oranian or Iberomaurusian backed blade technologies that were increasingly microlithic.…”
Section: Approximate Depth (M)supporting
confidence: 53%